2004
DOI: 10.3133/sir20045191
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Hydrologic Processes and Assessment of Rainfall-Runoff Models in Miami-Dade County, Florida

Abstract: "nuisance flooding" (Fennessey and others, 2001). In rural areas that include agricultural fields and undeveloped land, overland flow is controlled by the topography, land cover, and soil type; and overland flow can be appropriately simulated by two-dimensional diffusive overland flow models. This is particularly true in undeveloped 'A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
3
4
0
Order By: Relevance
“…An assumed DCIA , 1995, B, 2000, C, 2004, and D, 2008. Base modified from U.S. Geological Survey 1:2,000,000-scale digital data Base modified from U.S. Geological Survey 1:2,000,000-scale digital data , , B, 2000, , C, 2004, , and D, 2008 to TIA ratio of 25 percent is comparable to values calculated by Chin and Patterson (2005) for two catchment areas in the C-103 Basin (28.6 and 23.5 percent). Estimated DCIA for 1995 figure 6, ranges from 5.…”
Section: Surface Runoffsupporting
confidence: 54%
See 2 more Smart Citations
“…An assumed DCIA , 1995, B, 2000, C, 2004, and D, 2008. Base modified from U.S. Geological Survey 1:2,000,000-scale digital data Base modified from U.S. Geological Survey 1:2,000,000-scale digital data , , B, 2000, , C, 2004, , and D, 2008 to TIA ratio of 25 percent is comparable to values calculated by Chin and Patterson (2005) for two catchment areas in the C-103 Basin (28.6 and 23.5 percent). Estimated DCIA for 1995 figure 6, ranges from 5.…”
Section: Surface Runoffsupporting
confidence: 54%
“…As a result, surface runoff is controlled primarily by DCIA. Chin and Patterson (2005) found that the ratio of runoff to rainfall was in relatively close agreement with the percentage of DCIA in the catchments evaluated in the C-103 Basin, in the Homestead area south of Miami ( fig. 1).…”
Section: Surface Runoffsupporting
confidence: 54%
See 1 more Smart Citation
“…However, estimated specific yields based on longer time intervals are likely to be influenced by ground-water drainage associated with the numerous local drainage canals that penetrate the water table in south Florida. Chin and Patterson (2005) demonstrated that the extracted average specific yield using hourly data is close to the specific yield estimated using 15-min data (0.23 versus 0.26), while specific yields could not be estimated using daily rainfall data, since canal drainage was sufficiently efficient that negligible daily-average water-table changes resulted from daily-averaged storm events.…”
Section: Field Investigationmentioning
confidence: 76%
“…The volume of water added to the inner ring, to maintain the water level constant, is the volume of water that infiltrates the soil. Some minor operational modifications to the standard method were necessary because of the unique soil conditions in the study area, however, none of these changes are considered to add significant measurement error to the test results (Chin and Patterson, 2005).…”
Section: Field Investigationmentioning
confidence: 99%